Quality of life and its associated factors among COVID-19 recovered patients in South India: a cross-sectional analytical study - Ravel, Vanessa; Jayaseelan, Venkatachalam; Rajan S., Vignesh; Sivaji, Renjana; R., Arul Prasad; D., Mahadevan; Sekhar Kar, Sitanshu (International Journal Of Community Medicine And Public Health, 2025)
Background: Coronavirus disease (COVID-19), a pandemic affecting billions globally has impacted beyond physical health affecting mental and social well-being thereby affecting quality of life (QOL). This study aimed to explore the long-term sequalae of COVID-19 and compare QOL between those who had moderate or severe COVID-19 and those with mild disease and to assess the factors associated with their QOL. Methods: This cross-sectional analytical study was conducted among COVID-19 recovered patients between May-October 2022. Patients with oxygen saturation (SpO2)≤93 were considered as moderate to severe cases (group 1) and those with SpO2 >93 as mild cases (group 2). Participants selected by simple random sampling from the line-list of hospital records and their socio-demographic details were collected. QOL was assessed using validated English and Tamil version of world health organization QOL brief (WHOQOL-BREF) questionnaire. Results: Among the 1162 participants (581 in each group), majority were males (52.4%) with mean age of 48 (±16.4) years. Mean WHOQOL-BREF scores among participants was highest in social domain (71.7±9.2) and lowest in physical domain (58±8.2). Scores of all domains were significantly higher in group 2 than group 1. The predictors for lower QOL were skilled workers, people residing in rural areas, individuals above 30 years and presence of comorbidities in physical, psychological, social and environmental domains (p<0.001). Conclusions: COVID-19 has long-term effect on QOL of the patients. This study stresses the need for implementing strategies like post-COVID special clinics and counselling sessions to improve QOL of the affected individuals.